Inside Cover: Binding Cofactors with Triplex‐Based DNA Motifs (Chem. Eur. J. 47/2013). Issue 47 (18th November 2013) - Kröner, Christoph; Göckel, Anja; Liu, Wenjing; Richert, Clemens
<x xml:space="preserve">Abstract</x> Glowing when reaching body temperature The surface of a sepharose bead with immobilized triplex motifs releases bound NADH when approaching 37 °C. The NADH then induces bioluminescence. For more details, see the Full Paper by C. Richert et al. on page 15879 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>